Research of Electrical Response Communication Parameters on the Pulse Mechanical Impact with the Stress-Strain State of Concrete Under Uniaxial Compression; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Dann D. D. Denis Dmitrievich; Demikhova A.; Fursa T. V. Tatyana Viktorovna; Kuimova M. V. Marina Valerievna (2014, 2014)
Title screen